MENJAGA NETRALITAS ASN DALAM PEMILU - Nuraida Mokhsen (Bawaslu Provinsi Kepulauan Riau, 2019)
Neutrality of the State Civil Apparatus (ASN) is one of crucial issues that has received much attention in the holding of the 2015,2017 and 2018 as well as the legislative and presidential elections in 2019 due to the large amount of evidence which states that many ASN are not neutral. The Principles of ASN neutrality are regulated in KASN code of conduct. This code of ethics is important for realiing preofessional ASN not only in terms of competency ownership but also behavior in carrying out task. ASN has the right to vite but in carrying out its duties must be neutral from various political influences. Because ASN is often a role model in his life, so the behavior of ASN not allowed to show support to one of the Candidate Pairs. Moreover, to legislative candidates because this is also included in violations that can be subject to severe penalties in Election law.